Parkinson’s disease: A review from pathophysiology to treatment - Marino, Bianca L.B.; de Souza, Lucilene R.; Sousa, Kessia P.A.; Ferreira, Jaderson V.; Padilha, Elias C. [UNESP]; da Silva, Carlos H.T.P.; Taft, Carlton A.; Hage-Melim, Lorane I.S. (Bentham Science Publishers, 2020)
Parkinson's Disease (PD) is the second most common neurodegenerative disease in the elderly population, with a higher prevalence in men, independent of race and social class; it affects approximately 1.5 to 2.0% of the elderly population over 60 years and 4% for those over 80 years of age. PD is caused by the necrosis of dopaminergic neurons in the substantia nigra, which is the brain region responsible for the synthesis of the neurotransmitter dopamine (DA), resulting in its decrease in the synaptic cleft. The monoamine oxidase B (MAO-B) degrades dopamine, promoting the glutamate accumulation and oxidative stress with the release of free radicals, causing excitotoxicity. The PD symptoms are progressive physical limitations such as rigidity, bradykinesia, tremor, postural instability and disability in functional performance. Considering that there are no laboratory tests, biomarkers or imaging studies to confirm the disease, the diagnosis of PD is made by analyzing the motor features. There is no cure for PD, and the pharmacological treatment consists of a dopaminergic supplement with levodopa, COMT inhibitors, anticholinergics agents, dopaminergic agonists, and inhibitors of MAO-B, which basically aims to control the symptoms, enabling better functional mobility and increasing life expectancy of the treated PD patients. Due to the importance and increasing prevalence of PD in the world, this study reviews information on the pathophysiology, symptomatology as well as the most current and relevant treatments of PD patients.
Keywords: Dopamine; Dopaminergic agonists; Neuronal degeneration; Parkinson’s disease; Pathophysiology; Pharmacological treatment; Symptomatology